Pengaruh Model Pembelajaran Flipped Classroom dengan Media Interaktif Video Canva untuk Meningkatkan Motivasi dan Kemampuan Numerasi Siswa di SMK Negeri 3 Bengkalis - Marwaziah, Nirmala; Andrian, Dedek; Wahyuni, Reni; Widiati, Indah (Papanda, 2026)
Low level of students’ learning motivation and numeracy skills in the topic of the System of Linear Equations in Three Variables (SLETV) remains a challenge in mathematics learning at schools. Many students experience difficulties in understanding SLETV concepts because the instructional delivery tends to be abstract and less engaging; therefore, a learning approach that can enhance students’ readiness and interest prior to face-to-face classroom activities is required. This study aimed to examine the effect of the Flipped Classroom model assisted by Canva videos on students’ learning motivation and numeracy skills. This research employed a quasi-experimental method with a Nonequivalent Control Group Design, involving two classes selected through purposive sampling: an experimental class that received Flipped Classroom instruction and a control class that followed conventional learning. Data were collected through a learning motivation questionnaire and a numeracy skills test administered after the treatment. Data analysis was conducted using descriptive statistics and an independent samples t-test to determine differences in learning outcomes between the two groups. The results showed that the average learning motivation score of students in the experimental class reached 69.86, which was higher than that of the control class at 58.97. Meanwhile, the numeracy skills of the experimental class achieved an average score of 88.66, compared to 63.95 in the control class. The t-test results indicated a significance value of 0.000 for both variables, demonstrating a statistically significant difference between the two classes. These findings indicate that the Flipped Classroom model assisted by Canva videos effectively enhances students’ learning readiness, promotes active engagement during the learning process, and facilitates a better understanding of numerical concepts compared to conventional learning. This model can be considered an alternative instructional strategy to support the improvement of students’ learning motivation and numeracy skills.